2016
DOI: 10.5897/err2016.2937
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Reactive-Proactive Aggression Questionnaire in Turkish Adolescents

Abstract: The aim of this study was to adapt the Reactive-Proactive Aggression Questionnaire (RPQ), developed to measure two dimensions of aggression which are reactive and proactive, to Turkish and test the validity and reliability of the Turkish form. The study group consisted of 278 students in four junior high schools in Adana, Turkey, and 485 students in four high schools in Hatay, Turkey. One-factor and twofactor models were compared in the study of Confirmatory Factor Analysis conducted to examine the construct v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
1
4
0
1
Order By: Relevance
“…The present study examined the psychometric properties of the RPQ. The confirmatory factor analysis confirmed the same two-factor structure as in the original version of the RPQ [3], as well as in previous translations [14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study examined the psychometric properties of the RPQ. The confirmatory factor analysis confirmed the same two-factor structure as in the original version of the RPQ [3], as well as in previous translations [14][15][16][17][18][19].…”
Section: Discussionsupporting
confidence: 81%
“…In order to assess both dimensions of aggression, Raine and colleagues [3] developed the reactive and proactive aggression questionnaire (RPQ), a 23-item self-report questionnaire composed of a reactive aggression dimension and a proactive aggression dimension. Up to now, the RPQ has demonstrated satisfactory psychometric properties (i.e., factorial structure, internal consistency, construct validity) in several studies using the original English version [3], or translations into Dutch, Italian, Portuguese or Turkish [14][15][16][17][18][19]. Moreover, Cima et al [14] observed different relationships between the two forms of aggression and impulsivity (more strongly related to the reactive form of aggression) and psychopathic traits (more strongly related to the proactive form of aggression).…”
Section: Introductionmentioning
confidence: 99%
“…Example reactive aggression items include "Gotten angry when frustrated" and "Reacted angrily when provoked by others", whereas proactive aggression items include "Vandalized something for fun" and "Hurt others to win a game". The RPQ has been validated in adolescent and adult populations [Spielberger 1999], has demonstrated high reliability and internal consistency (Cronbach's alpha > 0.81) and can differentiate between community and forensic samples [39].…”
Section: Methodsmentioning
confidence: 99%
“…Bullying is a prevalent problem at all educational levels, with severe consequences for the participants [ 1 , 2 , 3 ]. This problem affects the psychosocial development of the students involved [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%